Clinically approved PEGylated nanoparticles are covered by a protein corona that boosts the uptake by cancer cells. Issue 29 (12th July 2017) - Papi, M.; Caputo, D.; Palmieri, V.; Coppola, R.; Palchetti, S.; Bugli, F.; Martini, C.; Digiacomo, L.; Pozzi, D.; Caracciolo, G.
Abstract : The protein corona boosts the cellular uptake of clinically approved PEGylated lipid nanoparticles in pancreas ductal adenocarcinoma cells. Abstract : Today, liposomes are an advanced technology of drug carriers with a dozen drugs in clinical practice and many more in clinical trials. A bottleneck associated with the clinical translation of liposomes has long been 'opsonization', i.e. the adsorption of plasma proteins at the liposome surface resulting in their rapid clearance from circulation. For decades, the most popular way to avoid opsonization has been grafting polyethylene glycol (PEG) onto the liposome surface. Recent studies have clarified that grafting PEG onto the liposome surface reduces, but does not completely prevent protein binding. In this work, we employed dynamic light scattering, zeta-potential analysis, one-dimensional sodium dodecyl sulfate polyacrylamide gel electrophoresis (1D-SDS-PAGE), semi-quantitative densitometry and cell imaging to explore the bio-nano-interactions between human plasma (HP) and Onivyde, a PEGylated liposomal drug that has recently been approved by the Food and Drug Administration (FDA) for the treatment of metastatic pancreatic ductal adenocarcinoma (PDAC). To properly evaluate the role of PEGylation, an unPEGylated variant of Onivyde was used as a reference. Collectively, our findings suggest that: (i) although PEGylated, Onivyde is not "stealth" in HP; (ii) surface chemistry is more important than PEGylation in controlling the bio-nano-interactions between Onivyde and plasma components. Of note is that the PC was found to boost the cellular uptake of Onivyde in the pancreas ductal adenocarcinoma cell line (PANC-1) thus suggesting its prominent role in its indication for PDAC treatment. Relevant implications for drug delivery and drug design are discussed.